Meaning making as a psychoeducational intervention to sustain families struggling with mental health issues - Lucia Zannini; Katia Daniele (University of Bologna, 2021)
In the psychiatric field, since the first decades of the XX century, some phenomenologically-oriented authors pointed out the importance of gathering patients' experience of illness and meaning making. In the current literature, a few interventions for people suffering from mental illness and their families/caregivers, aimed at supporting them in making meaning, are available. Yet, also relatives have to confront with the "loss" of mental health in their family, just like patients themselves. Relatives could therefore perceive the need to make meaning through narrating that loss. In this paper, we will report a few narrative-based interventions for relatives of patients suffering from mental health problems. We will conclude with some reflections, guided by phenomenological-existential pedagogy, which considers search for meaning as a fundamental educational practice, when caring for a wounded existence.